A consistent hybrid PDF method: implementation details and application to the simulation of a bluff-body stabilised flame. (6th April 2006) - Naud, B.; Jimenez, C.; Roekaerts, D.
PDF simulations of a bluff-body stabilised flame studied experimentally by Dally et al. have been performed using a hybrid Finite-Volume /particle method in combination with a local time-stepping algorithm. Using mixture fraction as only independent scalar and a flamelet chemistry model, satisfactory results for flow field and mean temperature are obtained. In the proposed hybrid method, the Finite-Volume submodel plays a leading role since it provides the mean velocity, mean velocity gradients, mean pressure gradient, mean dissipation and the gradients of Reynolds stresses used in the particle submodel, resulting in a low bias error. Details on the implementation are given, correction algorithms are presented and a new iteration averaging method is proposed. Despite an inconsistency in the treatment of triple correlation terms, the difference between the Reynolds stresses resolved in the Finite-Volume submodel and extracted from the ensemble of particles appears to be very small, demonstrating that the correction algorithms ensure consistency.